Fixation of a scapular body fracture in a 5 month old foal using three 4.5/5.0 mm locking compression plates. Issue 2 (5th December 2021) - Miyakoshi, Daisuke; Higuchi, Tohru; Ikeda, Hiroki; Sato, Masato; Yoshimura, Seiji
Abstract: Objective: To report a surgical technique and an outcome for the repair of a displaced, transverse scapular body fracture with locking compression plates (LCPs) in a colt. Animals: One 5 month old Thoroughbred colt. Study design: Case report. Methods: A colt sustained an unstable, comminuted, transverse fracture of the scapular body. Three 4.5/5.0 mm LCPs were used with 6.5 mm cancellous screws, 4.5 mm cortex screws, and 5.0 mm locking head screws. Implants were removed 2 months after surgery. Results: Surgical site infection was identified by purulent discharge at the distal aspect of the suture line 3 days after surgery. The surgical site infection resolved with daily lavage within 15 days after surgery. Three months after internal fixation of the scapular body fracture, the colt was sound and was turned out to pasture. One year later, the colt was sound and in training to be a flat racehorse. Conclusion: Repair of a scapular body fracture using LCP provided a good outcome with an early return to soundness. The LCP system can therefore be considered for the repair of scapular body fractures in small equids.